2017
DOI: 10.7897/2277-4343.085231
|View full text |Cite
|
Sign up to set email alerts
|

Gomutra (Cow Urine): A Multidimensional Drug Review Article

Abstract: Gomutra is important part of Indian tradition. It is not only holy but also has various important medicinal uses. Classical treatises in Ayurved i.e. Charaka, Sushruta and Vagbhata Samhita has described Ashta mutra (eight types of urine) along with their properties, indication and formulations. Cow urine is one of them. Cow urine is one of the five contents of Panchagavya which obtain from cow (urine, milk, ghee, curd and dung). Cow based treatment is called as Panchagavya Chikitsa (Cowpathy). In this modern e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 7 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Gulhane H et al (14) after analyzing different results on GA in various research articles observed that GA and its mixture was a multidimensional drug. It has been mentioned in the Ayurveda that FGA of indigenous cow is the most potent to be used as a drug.…”
Section: Discussionmentioning
confidence: 99%
“…Gulhane H et al (14) after analyzing different results on GA in various research articles observed that GA and its mixture was a multidimensional drug. It has been mentioned in the Ayurveda that FGA of indigenous cow is the most potent to be used as a drug.…”
Section: Discussionmentioning
confidence: 99%
“…Total organic carbon (TOC) of the mixtures was in the ranges of 245.5-359.0 mg g -1 dried sample and the order was T 0 >T 5 >T 4 >T 3 >T 2 >T 1 (Table 4). As cow urine is rich in minerals [17], TOC values were decreased with the increase in urine concentration in the mixtures.…”
Section: Total Organic Carbon (Toc)mentioning
confidence: 97%
“…Cow dung is abundantly available in India. Using cow dung as a bio-resource in wastewater treatment plants is safe and environmentally friendly because cow dung and cow urine are used to treat several human diseases in Indian herbal and natural treatment systems [39][40][41]. Activated sludge from the final settling tank has to take to feed the aeration tank.…”
Section: Oxidation Of Nitrite (No 2 ) Into Nitrate (No 3 )mentioning
confidence: 99%